2021
DOI: 10.3389/fped.2021.638540
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Pharmacological Support Among Preterm Infants in Chinese Referral Center Neonatal Intensive Care Units

Abstract: Objective: To describe cardiovascular pharmacological support in infants born at <34 weeks' gestation within the first postnatal week in Chinese neonatal intensive care units (NICUs).Design: A secondary analysis of data from a multicenter randomized controlled study (REIN-EPIQ). A questionnaire regarding cardiovascular support practices was also completed by all participating NICUs.Setting: Twenty-five tertiary hospitals from 19 provinces in China.Patients: All infants born at <34 weeks' gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous studies reported that the use of inotropes in preterm infants at an early age is associated with a higher risk of death, IVH, and BPD [ 16 18 ]. In particular, hypotension treatment in early life can reportedly affect changes in cerebral blood flow, causing IVH or hydrocephalus and long-term neurodevelopmental delays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the use of inotropes in preterm infants at an early age is associated with a higher risk of death, IVH, and BPD [ 16 18 ]. In particular, hypotension treatment in early life can reportedly affect changes in cerebral blood flow, causing IVH or hydrocephalus and long-term neurodevelopmental delays.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of EF in preterm infants is relatively high, and preterm infants with EF are more likely to have long-term complications, such as ventilator-associated pneumonia and BPD. [2][3][4][5] Previous studies reported that the use of inotropes in preterm infants at an early age of birth is associated with a higher risk of death, IVH, and BPD [11][12][13]. In particular, it has been reported that hypotension treatment in early life can affect changes in cerebral blood ow, causing IVH or hydrocephalus and long-term neurodevelopmental delays.…”
Section: Discussionmentioning
confidence: 99%
“…This study included all infants with birth weight (BW) lower than 1500 g admitted to the study sites within 7 days of birth from May 1, 2015, to April 30, 2018. Their clinical data were abstracted from the database of “Reduction of Infection in Neonatal Intensive Care Units using the Evidence-based Practice for Improving Quality (REIN-EPIQ)”, a multicenter NICU research database in China (Luo et al, 2021). Participants who did not receive enteral feeding or who received mixed feeding during hospitalization were excluded.…”
Section: Methodsmentioning
confidence: 99%